Profile of Tinea Corporis and Tinea Cruris in Dermatovenereology Clinic of Tertiery Hospital: A Retrospective Study - Selvia Yuliani Dwi Ratih Sanggarwati; Manik Retno Wahyunitisari; Linda Astari; Evy Ervianti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Tinea corporis and cruris are dermatophytes that infect the skin, and they are caused by Trichophyton sp., Microsporum sp., and Epidermophyton sp. Dermatophyte fungal-infect keratin-containing skin classified by the body’s location, such as tinea corporis (skin besides haired area, body, hands, or feet) and tinea cruris (groin & perineal region). Purpose: To evaluate the clinical profiles and treatments of tinea corporis and cruris at Dermatology and Venereology (DV) outpatient clinic Dr. Soetomo General Academic Hospital in 2018. Methods: A retrospective-descriptive study based on medical records of DV outpatient clinic Dr. Soetomo General Academic Hospital, Surabaya. Data collected from August to December 2019. Tinea corporis and cruris profiles evaluation based on age, sex, occupation, precipitating factors, complaints, illness duration, family history, lesion’s location and description, and therapy. Result: A total of 164 patients (35 tinea corporis, 76 tinea cruris, and 53 tinea corporis and cruris), predominantly female, age 46–55 years, came treatment less-than-a-month cases, excessive sweating, itching, tinea corporis lesion’s location on the face and body, tinea cruris in  groin, tinea corporis and cruris on body and groin, erythematous macules, firm borders, active margins, scales, central healing, positive KOH 10–20% examination, miconazole cream therapy 2%, griseofulvin therapy, griseofulvin oral and ketoconazole cream 2% combination therapy. Discussion: Tinea corporis and cruris are common in females as their history and symptoms supported by the characteristics of laboratory examination, the presence of hyphae in potassium hydroxide (KOH) 10–20%. Most patients were prescribed with oral griseofulvin, especially in large lesions cases.